On the Completeness and Minimality of Double and Unitary Systems in Morrey-Type Spaces - Seyidova, Fidan (Eurasian Mathematical Journal, 2021)
In this work, double and unitary systems of functions in Morrey type spaces Mp,α (−a, a) and Mp,α (0, a) are considered. A relationship between the completeness and minimality properties of these systems in these spaces is established.